Sliding mode control of flexible link manipulator using states and disturbance estimation. (1st January 2013) - Kurode, S.; Dixit, Prashant
This paper presents robust output feedback control for positioning a tip of flexible link manipulator (FLM). Sliding mode observer (SMO) is designed for an extended state system wherein disturbance is considered as an additional state. The SMO provides estimates of state and disturbance. The estimated disturbance is used to compensate the disturbance acting in the system by updating the control. The sliding mode control (SMC) is designed for position control of tip of FLM. The method is validated in both simulation and experiment.